Klasifikasi Algoritma Swarm Intelligence Dalam Perspektif Complex Adaptive System dengan Metode Uji Komparasi Statistik - Ketut Bayu Yogha Bintoro; Silvester Dian Handy Permana (Jurnal Teknologi dan Sistem Komputer, 2017)
This research aims to classify which SI algorithms have CAS or non-CAS criteria. The statistical comparative test method with 5 (five) characteristic test parameters was used as the proof approach that produces the classification. Based on the hypothesis that has been tested from 15 (fifteen) algorithms compared in this study, It was obtained that 8 of 15 (53.33%) algorithms has the majority of CAS characteristics, 3 of 15 (20%) algorithms has a minority of characteristics of CAS, and 4 out of 15 (26.66%) algorithms did not have CAS characteristics. The result can be a reference to understanding the characteristics of SI algorithms in the CAS and vice versa.